Beyond the Figure of the Husband: Television Serials and the Cultural Image of the Malayali - Aju Aravind
This paper tries to explore the marginality of women to public life in Kerala, an issue which is increasingly coming under critical scanner, the question of modernity and the representation of the popularly known Malayali women, in the popular televisions serials in Malayalam television channels and to trace the changes in the depiction of women characters in Malayalam television serials. Most of the Television serial in Malayalam are best known for being melodramatic and for its sentimental plot revolving around trivial day to day life of the Malayali women, especially the rift between the mother-in-law and the daughter-in-law, the adopted girl child and the step-mother, drift among sisters and so on and so forth. In this paper I argue that though most of the television serial are based on trivial happenings and events, but some of these melodramatic serials subtly project and share the anxieties of lost innocence, traditions and tries to retell the necessity to regain the lost Malayali values and ethics to the new generation. For the purpose of this I choose to discuss popular Malayalam serials like Bhaghyalakshi, Saaryu, Balamani, and Parasparam.